PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN IMPLIKASINYA PADA KINERJA PEGAWAI DINAS KESEHATAN KABUPATEN NAGAN RAYA - Arifuddin Arifuddin; Nasir Nasri; Sulaiman Sulaiman (Jurnal Magister Manajemen, 2018)
The study aims to determine the effect of job satisfaction and organizational commitment on organizational citizenship behavior and their impact on the employee performance of health offices of Nagan Raya district. The study conducted of 115 employees of the office. The data collected by questionnaire and then the data is analyzed by statistical means of structural equation model (SEM). The study found that job satisfaction and organizational commitment have a positive and significant effect on organizational citizenship behavior and employee performance. The Organizational citizenship behavior mediates the effect of job satisfaction and organizational commitment on the employee performance of the institution